The Clinico-Radiological Spectrum of Dyke-Davidoff-Masson Syndrome in adults - Zeynep Ozozen Ayas; Kıyasettin Asil; Ruhsen Ocal (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
Background: Dyke-Davidoff-Masson syndrome (DDMS) is characterized by cerebral hemiatrophy, epileptic seizures, contralateral hemiplegia/hemiparesis, and mental retardation. Aims: In this study, clinical and radiological investigations of seven patients who were diagnosed with DDMS as adults age were evaluated and discussed with the literature.                                                    Study Design: The medical records of 7 patients diagnosed with DDMS at hospital were retrospectively and cross-sectionally examined. Methods: Seven patients with DDMS diagnosed at adulthood between 2010 and 2016 were studied in our study. Patients' age, gender, etiological risk factors, presenting symptoms, lateralization, neurological examinations, computed tomography (CT) and / or magnetic resonance imaging (MRI) results were evaluated. Results: Seven patients (4 male, 3 female) were included in our study. The mean age ± SD of the patients was 46±21 years. Clinical presentation of 6 patients was epileptic seizure. One patient was presented with head trauma due to a fall. Three of the patients were experiencing seizures for the first time, and 3 had a known history of epilepsy. Severe mental retardation was detected in 2 of the patients presenting with seizures. Two patients had complex partial seizures, 3 patients had generalized tonic clonic seizures (GTC), and 1 had GTC and myoclonic seizure. Mental retardation was mild in 3 patients and severe in 2 patients. A congenital cause was detected in 1 patient in the etiologic investigation. In 2 patients, a childhood of menengitis history was determined to be the acquired cause. In four patients, the etiology was not identified. We observed left hemisphere involvement in 4 patients and right hemisphere involvement in 3 patients. Brain imaging was performed by CT only in 4 patients and by MRI only in 3 patients. All patients were diagnosed with DDMS at adulthood. All patients had hemiatrophy in unilateral hemisphere. Atrophy in basal ganglia was detected in 5 patients, and atrophy in brain stem in 4 patients. Calvarial thickening was observed in 4 patients. Hyperpneumonitization was seen in mastoid cells in 3 patients. Sinus hyperpneamonitization, including in the paranasal and frontal sinuses, was seen in 6 patients. Conclusion: DDMS is a rare syndrome diagnosed by clinical and radiological findings. Even it is diagnosed with epileptic seizure, hemiparesis, or mental retardation in childhood, it can also be diagnosed in adulthood symptomatically (mild-severe) or asymptomaticlly in adulthood with radiological findings, as it were in our study. As a result, DDMS is a syndrome with wide clinical and radiological spectra that can be variably symptomatic at different stages of life.